1994
DOI: 10.1002/jcb.240540302
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest by prostaglandin A1 at the G1/S phase interface with up‐regulation of oncogenes in S‐49 cyc cells

Abstract: Our previous studies have implied that prostaglandins inhibit cell growth independent of cAMP. Recent reports, however, have suggested that prostaglandin arrest of the cell cycle may be mediated through protein kinase A. In this report, in order to eliminate the role of c-AMP in prostaglandin mediated cell cycle arrest, we use the -49 lymphoma variant (cyc-) cells that lack adenylate cyclase activity. We demonstrate that dimethyl prostaglandin A1 (dmPGA1) inhibits DNA synthesis and cell growth in cyc- cells. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Growth arrest following PGA 2 treatment occurs primarily in the G 1 phase of the cell cycle, but the mechanisms responsible for eliciting this effect are not well understood. Along with several growthregulatory genes whose expression is altered following treatment with PGA 2 or with related prostaglandins (2,24,27), we previously reported that PGA 2 -mediated growth inhibition was associated with a rapid and dramatic loss in cyclin D1 expression (20). Here, we have investigated the mechanisms contributing to this down-regulation.…”
mentioning
confidence: 96%
“…Growth arrest following PGA 2 treatment occurs primarily in the G 1 phase of the cell cycle, but the mechanisms responsible for eliciting this effect are not well understood. Along with several growthregulatory genes whose expression is altered following treatment with PGA 2 or with related prostaglandins (2,24,27), we previously reported that PGA 2 -mediated growth inhibition was associated with a rapid and dramatic loss in cyclin D1 expression (20). Here, we have investigated the mechanisms contributing to this down-regulation.…”
mentioning
confidence: 96%
“…Several microarray-based studies have led to the identification of mRNAs whose transcription and/or steadystate levels are regulated by PGA 2 and other cyclopentenone PGs (2,44). We and others have previously reported several gene expression changes occurring during the PGA 2 -triggered stress response, including the inhibition of cyclin D1 levels and the potent up-regulation of p21 expression (36,45,(47)(48)(49). Further analysis of the PGA 2 -mediated down-regulation of cyclin D1 expression revealed that PGA 2 decreased the stability of the cyclin D1 mRNA, identified a specific 390-base 3Ј-UTR segment involved in cyclin D1 mRNA decay, and suggested a role for AUF1 in these destabilization events (49).…”
mentioning
confidence: 99%
“…The cyclopentenone prostaglandins A 1 (PGA 1 ) and A 2 (PGA 2 ) are potent inhibitors of growth in cultured cells (49,50) and exhibit antitumor activity in vivo (10,21,22,39,50). Growth arrest following PGA 2 treatment occurs primarily through a block in cell cycle progression at the G 1 -to-S transition, but the mechanisms responsible for eliciting this effect are still largely unknown (19). A number of genes (1,18,34) show altered expression following PGA 2 treatment, but the relationship between such changes in gene expression and the initiation and/or maintenance of the growth arrested state is unclear.…”
mentioning
confidence: 99%